Successful treatment with alectinib after crizotinib-induced esophageal ulceration. Issue 3 (June 2015) - Yoneshima, Yasuto; Okamoto, Isamu; Takano, Tomotsugu; Enokizu, Aimi; Iwama, Eiji; Harada, Taishi; Takayama, Koichi; Nakanishi, Yoichi
Highlights Esophageal injury has been reported as an adverse event associated with crizotinib. Alectinib is a highly selective ALK inhibitor and was approved in Japanin 2014. We describe the treatment with alectinib after crizotinib-induced esophageal ulcer.